Pharmacologically-Induced Neurovascular Uncoupling is Associated with Cognitive Impairment in Mice. Issue 11 (November 2015) - Tarantini, Stefano; Hertelendy, Peter; Tucsek, Zsuzsanna; Valcarcel-Ares, M Noa; Smith, Nataliya; Menyhart, Akos; Farkas, Eszter; Hodges, Erik L; Towner, Rheal; Deak, Ferenc; Sonntag, William E; Csiszar, Anna; et al.
There is increasing evidence that vascular risk factors, including aging, hypertension, diabetes mellitus, and obesity, promote cognitive impairment; however, the underlying mechanisms remain obscure. Cerebral blood flow (CBF) is adjusted to neuronal activity via neurovascular coupling (NVC) and this mechanism is known to be impaired in the aforementioned pathophysiologic conditions. To establish a direct relationship between impaired NVC and cognitive decline, we induced neurovascular uncoupling pharmacologically in mice by inhibiting the synthesis of vasodilator mediators involved in NVC. Treatment of mice with the epoxygenase inhibitor N -(methylsulfonyl)-2-(2-propynyloxy)-benzenehexanamide (MSPPOH), the NO synthase inhibitor l-NG-Nitroarginine methyl ester (L-NAME), and the COX inhibitor indomethacin decreased NVC by over 60% mimicking the aging phenotype, which was associated with significantly impaired spatial working memory (Y-maze), recognition memory (Novel object recognition), and impairment in motor coordination (Rotarod). Blood pressure (tail cuff) and basal cerebral perfusion (arterial spin labeling perfusion MRI) were unaffected. Thus, selective experimental disruption of NVC is associated with significant impairment of cognitive and sensorimotor function, recapitulating neurologic symptoms and signs observed in brain aging and pathophysiologic conditions associated with accelerated cerebromicrovascular aging.